Guilt Based Online Appeals for Donation by NGOs: Examined through the Integrated Marketing Communication Perspective - Hira, Ms. Navjiwan; Bawa, Dr. (Mrs.) Anupam (The journal of contemporary issues in business and government, 2021)
The current research makes a pioneering contribution by examining the existing literature on use of guilt in online appeals for donation by Non-Government Organisations(NGOs) using the Integrated Marketing Communication(IMC) perspective forwarded by Batra and Keller(2016) specifically their communication-matching model. Also, the present study examines the popularity of different communication content characteristics in online guilt appeals for donation, namely the type of guilt, type of appeal used- cognitive or emotional, type of guilt statements and application of donation-button through the content analysis methodology on 213 Indian NGO websites. The findings reveal that more than half the NGO websites use guilt as an appeal for raising donations and it is existential-guilt which is used 96.6 percent of the times. Further, the NGOs prefer emotive guilt appeals in visual form over cognitive appeals and statement of fact is the most used statement-type. However, the use of donation button is found only in 65.25 percent of the websites, thus highlighting the nascent stage of website development of Indian NGOs. Finally in the review of literature on ‘guilt and online donations’ conducted through the lens of IMC theory, a paucity of research is revealed and the study is concluded with suggestions to simultaneously examine the cross effects of a variety of online and offline media in the context of guilt appeals and a need is felt for more complex research designs and experiments in the e-philanthropy literature.